2015
DOI: 10.1007/s11104-015-2495-4
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic bacterial community composition in wheat (Triticum aestivum) is determined by plant tissue type, developmental stage and soil nutrient availability

Abstract: Reading's research outputs online Endophytic bacterial community composition in wheat (Triticum aestivum) is determined by plant tissue type, developmental stage and soil nutrient availability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
97
3
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 44 publications
(46 reference statements)
12
97
3
6
Order By: Relevance
“…This is only partly in line with a previous study showing that Pseudomonas, Rhizobium , and Bacillus were the most abundant genera in roots and shoots of sorghum21. Similar results were obtained by Robinson et al 7. who found that Pseudomonas and Bacillus dominated the endophyte community in wheat roots and leaves, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is only partly in line with a previous study showing that Pseudomonas, Rhizobium , and Bacillus were the most abundant genera in roots and shoots of sorghum21. Similar results were obtained by Robinson et al 7. who found that Pseudomonas and Bacillus dominated the endophyte community in wheat roots and leaves, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In total, 71 samples of the grass species L. perenne, D. glomerata , and F. rubra in two consecutive years were analyzed. Consistent with previous work72021, bacterial endophyte communities were dominated by five phyla. The genera Massilia, Pseudomonas , and Limnohabitans were predominant in the three grass species.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The authors concluded that flooding may affect the assembly of endophytic fungi in rice roots, but rice cultivars, geographical locations and soil types could also be important. In another study, Robinson et al (2016) reported on of the role of tissue type, growth stage and soil fertilizers in shaping the root and leaf bacterial endophyte communities of winter wheat (Triticum aestivum cv. Hereward), demonstrating that the plant microbiome is shaped by a complex interplay between biotic and abiotic factors.…”
Section: Endophytes Microbiome and Extreme Conditionsmentioning
confidence: 99%
“…Some studies have also assessed the effect of various factors, such as tissue type, plant developmental stage, and nutrient availability, on the diversity of communities (e.g., [68]). Evaluations of rhizospheric communities have followed the same pattern, reflecting highly specific conditions; therefore, no attempts to estimate the total number of endophytic or rhizospheric species that are present on the planet have been reported.…”
Section: Microbial Diversity: What Do We Have?mentioning
confidence: 99%